Toxicological Profile of Ultrapure 2,2′,3,4,4′,5,5′-Heptachlorbiphenyl (PCB 180) in Adult Rats - Viluksela, Matti (Public Library of Science, 2014)
PCB 180 is a persistent non-dioxin-like polychlorinated biphenyl (NDL-PCB) abundantly present in food and the environment. Risk characterization of NDL-PCBs is confounded by the presence of highly potent dioxin-like impurities. We used ultrapure PCB 180 to characterize its toxicity profile in a 28-day repeat dose toxicity study in young adult rats extended to cover endocrine and behavioral effects. Using a loading dose/maintenance dose regimen, groups of 5 males and 5 females were given total doses of 0, 3, 10, 30, 100, 300, 1000 or 1700 mg PCB 180/kg body weight by gavage. Dose-responses were analyzed using benchmark dose modeling based on dose and adipose tissue PCB concentrations. Body weight gain was retarded at 1700 mg/kg during loading dosing, but recovered thereafter. The most sensitive endpoint of toxicity that was used for risk characterization was altered open field behavior in females; i.e. increased activity and distance moved in the inner zone of an open field suggesting altered emotional responses to unfamiliar environment and impaired behavioral inhibition. Other dose-dependent changes included decreased serum thyroid hormones with associated histopathological changes, altered tissue retinoid levels, decreased hematocrit and hemoglobin, decreased follicle stimulating hormone and luteinizing hormone levels in males and increased expression of DNA damage markers in liver of females. Dose-dependent hypertrophy of zona fasciculata cells was observed in adrenals suggesting activation of cortex. There were gender differences in sensitivity and toxicity profiles were partly different in males and females. PCB 180 adipose tissue concentrations were clearly above the general human population levels, but close to the levels in highly exposed populations. The results demonstrate a distinct toxicological profile of PCB 180 with lack of dioxin-like properties required for assignment of WHO toxic equivalency factor. However, PCB 180 shares several toxicological targets with dioxin-like compounds emphasizing the potential for interactions.